Keberdayaan Perempuan: Konsep Pemberdayaan dalam Pembangunan Masyarakat Berbasis Gender - Ernawati S. Kaseng (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2023)
Women's empowerment is an effort to reallocate power through changing social structures. The percentage of women is much higher when compared to the number of men, but in fact the level of female work participation in Indonesia is still relatively low when compared to the level of work of men. The study method used, namely the literature study method where the data obtained is compiled, so that conclusions are obtained. Data type, that is, using secondary data. Data collection techniques, namely through the stages of taking data from the library, reading, recording, and processing data from the material obtained. The study of this article shows that women's empowerment is an effort to reallocate power through changes in social structure that can be done through various approaches, concepts, strategies and principles of empowerment, one of which is gender-based community empowerment. Through activities rmpowerment is expected to occur non-formal education to change the mindset and perspective of women or housewives which will ultimately educate them to be diligent, creative and innovative to develop their abilities in accordance with their talents so as to encourage people's economic development and increase family economic income. This is of course so that women or housewives can be independent and not depend entirely on their husbands to meet the daily needs of their families.